Contextual Enablers and Hindrances of Girl Child Participation in STEM Education in a Kenyan County: A Case Study (Proceedings of the International Conference on Future of Education, 2021)
In Kenya, student performance in sciences and Mathematics is still low compared to artoriented disciplines. The poor performance has affected not only the Girl child’s interest in thesedisciplines but also the number of girls that take STEM-oriented programs at tertiary levels. Severalmitigating measures have been enacted although the situation has not changed much. This paperreports a study that explored contextual enablers and hindrances of Girl Child participation in STEMeducation in a Western Kenyan county. The study employed a case study approach by administeringstructured questionnaires, interview schedule and focused group discussion guide for data collection.The data were analyzed using both quantitative and qualitative methods and revealed that: 1) lessondevelopment that connected science concepts to activities in the local context motivated andimproved girl child’s participation and performance in contextualized learning activities and 2),familiarity with the materials and tools used in planning and implementing contextualized learningactivities evoked the girl child’s enthusiasm and courage to exchange knowledge and ask morecuriosity focused questions. Also revealed were hindrances including: 1) teachers’ initial trainingthat did not prepare them for this way of teaching and it was not and has not been modeled for themduring their pre-service education or the ongoing professional development workshops; and 2) theexam driven nature of the curriculum serving as a hindrance to teacher innovation and creativity ininstructional techniques. The study recommends a more creative and innovative teacher trainingsystem and focused research to monitor girl child participation and performance in STEM education.
Keywords: Contextualized learning; Girl Child; STEM education; performance